2021
DOI: 10.1186/s12936-021-03835-7
|View full text |Cite
|
Sign up to set email alerts
|

Malaria prevalence and long-lasting insecticidal net use in rural western Uganda: results of a cross-sectional survey conducted in an area of highly variable malaria transmission intensity

Abstract: Background Long-lasting insecticidal nets (LLINs) remain a cornerstone of malaria control, but strategies to sustain universal coverage and high rates of use are not well-defined. A more complete understanding of context-specific factors, including transmission intensity and access to health facilities, may inform sub-district distribution approaches and tailored messaging campaigns. Methods A cross-sectional survey of 2190 households was conducted… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…The tropical climate allows for year-round malaria transmission interspersed with semi-annual peaks after the rainy seasons ( 33 ). Malaria prevalence from the most recent Malaria Indicator Survey in the mid-western region of Uganda, which encompasses Bugoye, was estimated at 18% among children under 5 years of age ( 34 ), although more recent studies in the sub-county demonstrate substantial geographic heterogeneity ( 35 ).…”
Section: Methodsmentioning
confidence: 99%
“…The tropical climate allows for year-round malaria transmission interspersed with semi-annual peaks after the rainy seasons ( 33 ). Malaria prevalence from the most recent Malaria Indicator Survey in the mid-western region of Uganda, which encompasses Bugoye, was estimated at 18% among children under 5 years of age ( 34 ), although more recent studies in the sub-county demonstrate substantial geographic heterogeneity ( 35 ).…”
Section: Methodsmentioning
confidence: 99%
“…However, it has also been suggested that sufficient biting still occurs late at night within households with LLINs for transmission to occur [ 4 , 5 ]. The high prevalence of LLIN during this study was almost certainly the result of a national LLIN mass distribution campaign in 2020–21 [ 40 ] and was significantly higher than observed in the region in January-March 2020, when coverage was found to be 64.7% [ 17 ]. In addition, utilization of protective measures within the household (e.g., LLIN and installation of screening) may reflect both actual risk and the perceived risk of the homeowner.…”
Section: Discussionmentioning
confidence: 99%
“…The area is characterized by its varied geography, with deep river valleys and steep hillsides reaching elevations reaching 2500 m. The climate in western Uganda permits year-round malaria transmission with semi-annual peaks after the rainy seasons in May and November [ 14 , 15 ] driven by a mixture of Anopheles gambia e, Anopheles arabiensis , and Anopheles funestus , among others [ 16 ]. The most recent MIS in the Tooro subnational region (2018–2019), which includes the sub-county, reported a PfPR of 7.3% although rates of 30% are reported in low-lying villages located along the river basins [ 11 , 17 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…falciparum parasitemia rates (PfPR) of 17.4% and 7.3%, respectively [ 39 , 40 ]. However, in a recent cross-sectional survey of more than 2,100 households in the Bugoye Sub-County, we found that the PfPR among children 2 to 8 years of age was upwards of 30% in many of the low-elevation villages [ 41 ]. We will recruit and enroll participants from these high transmission villages located along the river basins.…”
Section: Methodsmentioning
confidence: 99%